2010
DOI: 10.1002/aoc.1649
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a new salphen‐type titanium complex and its application in ethylene polymerization and copolymerization

Abstract: TiCl 2 [salphen(di-tBu)] was synthesized, characterized and employed as pre-catalyst in ethylene homo-and copolymerization with propylene, 1-octene and 10-undecen-1-ol. X-ray diffraction study on the titanium complex revealed a distorted octahedral coordination of the central metal with a trans-Cl, cis-O, cis-N arrangement. The complex combined with MAO afforded moderate catalytic activities in ethylene polymerization. Furthermore the catalyst not only copolymerized ethylene with apolar monomer (propylene and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As mentioned in section , those traditional Schiff base ligands such as salen and salphen tend to adopt the geometry cis -N/ cis -O/ trans -X with group 4 metals, ,,,,, whereas in order for efficient olefin insertion to occur, the X ligands (potential reaction site) are preferably placed cis to each other.…”
Section: Polymerization With Tetradentate [Onno] Phenoxy−imine Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…As mentioned in section , those traditional Schiff base ligands such as salen and salphen tend to adopt the geometry cis -N/ cis -O/ trans -X with group 4 metals, ,,,,, whereas in order for efficient olefin insertion to occur, the X ligands (potential reaction site) are preferably placed cis to each other.…”
Section: Polymerization With Tetradentate [Onno] Phenoxy−imine Complexesmentioning
confidence: 99%
“…Among the phenoxy−azo and phenoxy−imine chelating compounds, which Taylor screened for ethylene polymerization in conjunction with TiCl 4 /Et 2 AlCl (see section ), bridged phenoxy−imine ligands, salen, salpen, and salphen, were examined, but they were considered to be inactive (rather correctly in retrospect) . The investigation on group 4 metal complexes of salen, salpen, or salphen for olefin polymerization was resumed after a long pause in the late 1990s, which is compiled in Table . ,,,,,,,,,,, Repo and co-workers prepared a Zr salen complex, (L FI−FI )ZrCl 2 (thf) ( 314 ), and determined their solid state structures by X-ray crystallography, which revealed that the chlorides were trans to each other and the THF molecule occupied the seventh coordination site in the ONNO plane . The trans -Cl atoms of some Zr and Hf acen complexes were rearranged cis to each other upon removal of the THF molecule, however, the Zr salen complex exhibited similar low activities (120−130 g-polymer/(mmol-M·h) at 80 °C, 0.5 MPa) with and without the coordinated THF.…”
Section: Polymerization With Tetradentate [Onno] Phenoxy−imine Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the M w values of the copolymer were extremely higher than the reported results. [36][37][38][39] In the differential scanning calorimetry (DSC) results of the obtained copolymers, the T m values decreased (Fig. 3).…”
Section: Communicationmentioning
confidence: 97%